What the Secretary said next: `Public rhetorical leadership' in the Australian public service - Grube, Dennis (2011)
Every year, senior departmental secretaries in Australia deliver keynote speeches to a range of audiences. What are these secretaries talking about, and to whom are they directing their comments? This article will examine keynote addresses by the secretaries of the two key central agencies in Australia - the Department of Prime Minister and Cabinet and The Treasury - over the calendar years 2009 and 2010. I argue that `public rhetorical leadership' by secretaries poses challenges for traditional undertakings of Westminster governance. Utilising the concepts of public value theory, the significance of this `public rhetorical leadership' is assessed in terms of its impacts on policy implementation and questions of accountability. - Reproduced.
Keywords: Civil service